Delayed Chemotherapy-Induced Nausea and Vomiting: Pathogenesis, Incidence, and Current Management - Rapoport, Bernardo L. (Frontiers in Pharmacology, 2017)
Even when chemotherapy-induced nausea and vomiting (CINV) can be effectively controlled in the acute phase, it may still occur in the delayed phase. Identifying at-risk patients is complex and requires consideration of clinical, personal, demographic, and behavioral factors. Delayed CINV has a significant detrimental effect on patients’ daily life and is responsible for significant healthcare resource utilization. Patients who do not experience acute CINV are not necessarily exempt from delayed CINV, and healthcare professionals have been shown to underestimate the incidence of delayed CINV. Failure to protect against CINV during the first cycle of chemotherapy is the most significant independent risk factor for delayed CINV during subsequent cycles. Addition of a neurokinin-1 receptor antagonist to antiemetic prophylactic regimens involving a 5-hydroxytryptamine type 3 receptor antagonist and a corticosteroid helps to ameliorate delayed CINV, particularly vomiting. Netupitant and rolapitant are second-generation neurokinin-1 receptor antagonists that provide effective prophylaxis against delayed chemotherapy-induced vomiting and also have an antinausea benefit. All of the neurokinin-1 receptor antagonists with the exception of rolapitant inhibit or induce cytochrome P450 3A4 (CYP3A4), and a reduced dose of dexamethasone (a CYP3A4 substrate) should be administered with aprepitant or netupitant; by contrast, this is not necessary with rolapitant. Here we review specific challenges associated with delayed CINV, its pathophysiology, epidemiology, treatment, and outcomes relative to acute CINV, and its management within the larger context of overall CINV.